1995
DOI: 10.1007/bf00312379
|View full text |Cite
|
Sign up to set email alerts
|

Venous invasion as a prognostic factor in colorectal cancer

Abstract: Venous invasion as a prognostic factor was evaluated in 124 patients with colorectal cancer. By classifying the patients as having either negative to mild invasion or moderate to marked invasion, a significant correlation was found between the degree of venous invasion and clinicopathological variables such as lymphatic invasion, lymph node metastasis, liver metastasis, and DNA ploidy. Significantly more favorable survival was seen in those with a lower degree of vascular invasion; however, of the six prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 23 publications
0
6
1
1
Order By: Relevance
“…In this study, the incidence of venous invasion in the three groups was higher than that in previous reports 8–12 . However, these conflicting results are thought to reflect differences in the definition of venous invasion, the use of elastic staining techniques, and the number of sections used for each investigation 7 . For most venous invasion, it is easy to detect the presence of cancer cells in encircled elastic tissue fibres by using Weigert’s resorcin–fuchsin staining.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…In this study, the incidence of venous invasion in the three groups was higher than that in previous reports 8–12 . However, these conflicting results are thought to reflect differences in the definition of venous invasion, the use of elastic staining techniques, and the number of sections used for each investigation 7 . For most venous invasion, it is easy to detect the presence of cancer cells in encircled elastic tissue fibres by using Weigert’s resorcin–fuchsin staining.…”
Section: Discussioncontrasting
confidence: 69%
“…The influence of venous invasion on survival was first described by Brown and Warren 14 . Since then, many reports have proven the importance of venous invasion for visceral metastasis 1–7 . Talbot 13 reported the first series in which both intramural and extramural types of venous invasion were examined by elastic tissue stains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine vessel invasion more objectively, staining with Elastica van Gieson or VB for elastic fibers of intratumoral veins should be performed in addition to normal HE staining (Inada, Shimokawa et al, 1991;Tsuchiya, Ando et al, 1995). When such double staining was performed in the present study, we found a statistically significant difference between vessel invasion of hepatic metastasis and prognosis, and demonstrated a relationship with recurrence of metastasis in the remnant.…”
Section: Discussionmentioning
confidence: 53%
“…La survie des tumeurs coliques opérées en occlusion même en l'absence d'envahissement ganglionnaire est inférieure à celle des tumeurs limitées à la sousmuqueuse. Les envahissements vasculaires veineux et lymphatiques ne sont pas retrouvés dans plusieurs études comme des facteurs pronostiques indépendants en analyse multivariée [16,17]. L'invasion périveineuse serait à l'origine de récidives et de métastases par voie hématogène, mais son caractère indépendant en termes de pronostic n'a pas été clairement démontré.…”
Section: Autres Facteurs De Mauvais Pronosticunclassified